ANALISIS LOYALITAS PELANGGAN BERDASARKAN DIVERSIFIKASI PRODUK, HARGA, DAN KEPUASAN PELANGGAN (Studi Empiris Loyalitas Pelanggan Pada Mie Apong Sampurna Gebang Jember) - Ayuningtyas, Erika; Santoso, Budi; Winahyu, Pawestri (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Customer loyalty is an important aspect that is considered by a company, as well as in the food business, along with the development of the culinary business in the city of Jember, the competition faced by Mie Apong Sampurna Gebang Jember is also getting tougher, to overcome competitive competition and also maintain customer loyalty. it is necessary to have a strategy, namely through product diversification, price and customer satisfaction to continue to increase customer loyalty so that they can continue to compete and open up opportunities to expand their business. This research was conducted on Mie Apong Sampurna Gebang Jember customers. The purpose of this study was to measure whether there is an effect of product diversification, price, and customer satisfaction on customer loyalty at Mie Apong Sampurna Gebang Jember. This type of research is quantitative associative research. The population in this study were customers of Mie Apong Sampurna Gebang Jember. The data analysis technique used to test the hypotheses in this study used multiple linear regression analysis with the t test and the coefficient of determination (R2) which was processed using the Statistical Product and Service Solution (SPSS) 23 program. Data collection techniques used questionnaires, observations and interviews. The sample of this research is 150 respondents of Mie Apong Sampurna Gebang Jember customers using purposive sampling technique which aims to determine the respondent's perception of each variable. The results of this study prove that Product Diversification, Price, and Loyalty have a significant effect on Customer Satisfaction of Mie Apong Sampurna Gebang Jember